A novel drifter designed for use with a mounted Acoustic Doppler Current Profiler in shallow environments. (20th August 2013) - Mullarney, Julia C.; Henderson, Stephen M.
<x xml:space="preserve">Abstract</x> We present a novel design for a surface drifter, mounted with a pulse‐coherent Acoustic Doppler Current Profiler (ADCP) for measuring near‐surface (depths 0.18–1 m) flows. During repeated drifter deployments over the tidal flats of Skagit Bay, the mounted ADCP recorded high quality and high resolution profiles of velocity in depths as shallow as 0.4 m. Depth‐dependent velocities revealed regions of vertically sheared currents and wave motions not resolved by surface drifters alone. Although the cost of ADCPs is substantial, the drifter bodies were low cost, robust, and of simple construction.